Improvement of lipid profile after 6 months of self-initiated, multicomponent physical activity in a previously inactive 62-year-old patient: a case report - Puchalski, Konrad; Radwańska , Natalia; Polakowska, Izabela; Labut , Bartłomiej; Popielec-Jakubiec, Katarzyna; Kabak , Miraslau; Bęben, Agata; Glowacka , Zuzanna; Neumann, Wojciech (Quality in Sport, 2026)
Background: Hypercholesterolemia has become one of the main, modifiable risk factors to develop atherosclerotic cardiovascular diseases.Diet modification and lipid‑lowering pharmacotherapy are standard of care, but some patients decline these options. Regular physical activity can improve lipid profile and blood pressure without any medications and diet . Aim: To evaluate the effect of regular, multicomponent physical activity, without concurrent dietary change or pharmacotherapy on lipid profile, blood pressure and body mass in a previously inactive 62‑year‑old man. Material and methods: A 62‑year‑old male patient with elevated total cholesterol (TC) and LDL‑cholesterol (LDL‑C) , previously sedentary, declined diet modification and lipid‑lowering medications. In April 2025 he initiated a multicomponent program: running ( 5 km, three times per week), swimming (twice per week), and resistance training (twice per Results: Over 6 months, TC decreased from 217 to 174 mg/dL (−19.8%; 5.61 to 4.50 mmol/L), LDL‑C from 147 to 116 mg/dL (−21.1%; 3.81 to 3.00 mmol/L), and HDL‑C increased from 49 to 54 mg/dL (+10.2%; 1.27 to 1.40 mmol/L). Non‑HDL cholesterol declined from 168 to 120 mg/dL (−28.6%; 4.35 to 3.10 mmol/L). Blood pressure decreased from 135/85 to 122/80 mmHg, and body mass from 85 to 83 kg (−2.4%). Conclusions: In this previously inactive adult, 6 months of systematic, multicomponent physical activity without dietary or pharmacologic changes was associated with clinically meaningful improvements in LDL‑C, non‑HDL cholesterol, HDL‑C, blood pressure and body mass. The case supports multicomponent exercise as a practical, non‑pharmacologic intervention in primary prevention for patients declining standard lipid‑lowering strategies.